Bicornual Total Uterine Prolapse in a Domestic Shorthair Cat - A Case Report - S. Alagar,; S. Rangasamy,; R. Arun,; A. Methai,; P.N.Richard Jagatheesan, (The Indian Veterinary Journal, 2024)
A six year old Domestic Short Hair (DSH) cat was presented to the Small Animal Gynecology and Obstetrical Unit at the Teaching Veterinary Clinical Complex, Veterinary College and Research Institute (VCRI), Theni. The cat had a history of total uterine prolapse, severe straining and a prolapsed mass was hanging from the vagina for the past 24 hours. Upon examination, the prolapsed mass was observed to be dry, reddish, edematous and protruding outside the vaginal cavity. All other vital parameters were within the normal range.Under sedation, the prolapsed mass was cleansed with saturated lukewarm water and a pressure bandage soaked in 50% Dextrose was applied over the uterine horns for 15 minutes. Following this, the uterine mass was further cleaned with normal saline and a metronidazole solution. Aseptic manual repositioning was then performed after applying lignocaine gel with K-Y lubricant.Upon successful repositioning of the uterine horns, a vulval lip purse-string  stay suture was applied and a single dose of subcutaneous Inj. Cefovecin antibiotic was administered. Additionally, the Inj. Oxytocinintramuscularly and Calcium gluconate 10%administered with 5% DNS to promoting uterine contractions and aiding in the reduction of the prolapsed uterus.The cat recovered uneventfully after five days of treatment.